2013
DOI: 10.1371/journal.pone.0061886
|View full text |Cite
|
Sign up to set email alerts
|

The Second Transmembrane Domain of P2X7 Contributes to Dilated Pore Formation

Abstract: Activation of the purinergic receptor P2X7 leads to the cellular permeability of low molecular weight cations. To determine which domains of P2X7 are necessary for this permeability, we exchanged either the C-terminus or portions of the second transmembrane domain (TM2) with those in P2X1 or P2X4. Replacement of the C-terminus of P2X7 with either P2X1 or P2X4 prevented surface expression of the chimeric receptor. Similarly, chimeric P2X7 containing TM2 from P2X1 or P2X4 had reduced surface expression and no pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Recently, it has been demonstrated that the Q332P, Y336T, and Y343L mutants of P2X7R exhibited decreased dye uptake, whereas the V335T, S342G, and S342A mutants exhibited enhanced dye uptake during sustained agonist application (Sun et al . ). Another study revealed that the T348K, D352N, and D352K mutant receptors displayed increased relative permeability to chloride ions and promoted the entry of the large negative dye fluorescein‐5‐isothiocyanate (Browne et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, it has been demonstrated that the Q332P, Y336T, and Y343L mutants of P2X7R exhibited decreased dye uptake, whereas the V335T, S342G, and S342A mutants exhibited enhanced dye uptake during sustained agonist application (Sun et al . ). Another study revealed that the T348K, D352N, and D352K mutant receptors displayed increased relative permeability to chloride ions and promoted the entry of the large negative dye fluorescein‐5‐isothiocyanate (Browne et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Sun et al . ). The role of TM1 in the dilation of the P2X7R pore has also been suggested (Nicke et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, subtype-specific motifs are mainly located in the C-terminus, such as motifs 27 and 35 in mammalian P2X6, which is thought to be involved in desensitization [56]. A series of P2X7-specific motifs (motifs 19,24,23,20,16, and 21) was found, which can constitute a longer TM2 domain enabling P2X7 receptors to provide a pathway that allows the passage of larger organic cations [57,58]. In addition, some primitive species (Aqu-p2xa, Sko-p2xa, Nve-p2xa) share a series of conserved motifs with advanced species, while some homologous short motifs were also detected in Fig.…”
Section: Phylogenetic Analysis Of the Putative P2x Genesmentioning
confidence: 99%
“…The cytolytic activity of human P2X7R (hP2X7R) has been attributed to a time-dependent dilation of the integral ion channel based on macroscopic current recordings of various cell types (7)(8)(9)(10)(11). Particularly revealing was the observation that substituting T348 and D352 with basic residues in the channellining second transmembrane domain (TM2) of the rat P2X7R (rP2X7R) simultaneously increased the permeability of the normally cationic channel for Cl − and an acidic fluorescent dye with an effective diameter of >10 Å (12).…”
mentioning
confidence: 99%